(untitled) (JSSIT: Jurnal Sains dan Sains Terapan, 2024)
Ensis sp. is a primary source of protein from the Nyumbun Tradition in Jambi Province, and it is becoming solid waste after tradition. This study explored the effect of calcination temperature on green powder derived from Ensis sp. shell waste. Before characterization, the powder was treated at room temperature, 800 °C, and 900 °C. After that, the powder material was studied using Atomic Absorption Spectroscopy (AAS) and Scanning Electron Microscope (SEM) instruments. The material was shifted using a 200 mesh sieve. Temperature of 800 and 900 °C showed similar Ca content of 443 and 447,6 mg/g, respectively. The morphology of the two samples was different due to the other temperature conditions used. Higher temperatures induce decomposition, leading to a decrease in particle size. The product of this process could be used as a promising heterogeneous catalyst, so it reduced the existence of shell waste. Keywords: shells waste, Ensis sp, heterogeneous catalyst